ADOPTION OF AUTOMATED CHAT-BOTS AND FIRM PROFITABILITY OF DEPOSIT MONEY BANKS IN NIGERIA (Journal of Global Accounting, 2026)
This study investigated the effect of adoption of automated chatbot on financial performance of deposit money banks in Nigeria. The specific objective was to determine the effect of automated chatbot on return on investment and earnings per share of deposit money banks in Nigeria. The study adopted ex-post facto research design. The population of the study consisted of all the (13) quoted deposit money banks in Nigeria Exchange Group up to December, 2024. Ten (10) deposit money banks was sampled using purposive sampling technique. Secondary data for the study were collected from the banks’ annual reports over a period of 12 years from (2013 – 2024). Descriptive test was carried out, followed by panel least square regression which revealed that: automated chatbot has a significant positive effect on the return on investment of deposit money banks in Nigeria (β = 0.051208; p-value = 0.000); automated chatbot has a significant positive effect on earnings per share of deposit money banks in Nigeria (β = 3.029733; p-value = 0.000). In conclusion, chatbot implementation contributes to increased profitability of Nigerian deposit money banks by enhancing operational efficiency and reducing costs. The study recommends that bank executives and decision-makers should allocate more resources towards the implementation, optimization, and scaling of chatbot technology in order to improve operational efficiency, reduce costs, and potentially enhance asset utilization.
Keywords: Automated Chatbot; Firm profitability; Return on investment; Earnings Per Share